Answer:
-387
Step-by-step explanation:
First term (T1) = -21 = a
second term (t2) = - 27
common difference (d) = t2 - t1 = - 27 + 21 = - 6
Now
Tn = a + ( n - 1) d
T62 = - 21 + ( 62 - 1 ) - 6
= - 21 -366
= -387
Answer:
Two negative make a positive so this equation is basically 39 = n + 12 so you need to subtract 12 from each side. This makes it n = 27
Hope this helps!
Answer:
30
Step-by-step explanation:
8x6 is 48
7x6 is 42
so 5x6 is 30
Answer:
Step-by-step explanation:
<u>Three faces are equal triangles with:</u>
- base = 8 units, height = 6 ft
<u>The base is a triangle with:</u>
- base = 8 ft, height = 6.9 ft
<u>Surface area is sum of areas of 4 faces:</u>
- S = 3*(1/2*8*6) + 1/2*8*6.9 = 99.6 ft²
Answer:
X/2 = 61.2
X=122.4
Step-by-step explanation:
Ok so we know that a number was halved so we can use x and equaled to 61.2 so we can do x/2 = 61.2